2018
DOI: 10.1177/1473871618754343
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of linear and mosaic diagrams for set visualization

Abstract: Linear diagrams have been shown to compare favourably to better known forms of set visualization, such as Venn and Euler diagrams, in supporting non-interactive assessment of set relationships. Recent studies that compared several variants of linear diagrams have demonstrated that users perform best at tasks involving identification of intersections, disjointness and subsets when using a horizontally drawn linear diagram with thin lines representing sets and employing vertical lines as guide lines. The essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Although our current prototype has a limited number of interactive tools, these could be extended easily along the lines of interactive functionality that we have identified. We are also aiming to investigate a number of alternatives to the time-sets visualization, including the use of space-filling mosaics [23], which have been shown to be more effective than linear diagrams for some tasks involving visual comparisons of set relationships [24], but without involving comparisons across multiple axes or time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our current prototype has a limited number of interactive tools, these could be extended easily along the lines of interactive functionality that we have identified. We are also aiming to investigate a number of alternatives to the time-sets visualization, including the use of space-filling mosaics [23], which have been shown to be more effective than linear diagrams for some tasks involving visual comparisons of set relationships [24], but without involving comparisons across multiple axes or time.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of the visual element of line length [5] to represent cardinality in linear diagrams would be an obvious choice, and has previously been suggested [13,24], it has not been widely adopted or utilized in existing visualizations. In most cases, the drawing algorithm used for creating linear diagrams aims to create the most compact, and the least segmented, version of the diagram using multiples of a basic (shortest) unit of line length for each intersection, without representing cardinalities.…”
Section: Set Visualizationsmentioning
confidence: 99%
“…Matrixbased methods scale well, but have a strong dependency on row and column ordering, are less intuitive for nonexperts, and require interaction with a non-trivial interface for the more complex set visualization tasks. Closely related are linear diagrams [7], [35], [36], where again each set is a row in a table. The columns, however, do not represent individual elements, but rather non-empty set intersections.…”
Section: Set Visualization Techniquesmentioning
confidence: 99%
“…Further evaluations considered techniques such as Euler diagrams, linear diagrams, and mosaic diagrams, all of which do not represent individual elements and thus used only set-based tasks [3], [7]. They showed that linear diagrams outperformed Euler diagrams and were on par with mosaic diagrams.…”
Section: Evaluations Of Set Visualization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation